Carbon Dots’ Antiviral Functions Against Noroviruses - Xiuli Dong (Nature Portfolio, 2017)
Abstract This study reported the first assessment of carbon dots’ (CDots) antiviral activity to human norovirus virus-like-particles (VLPs), GI.1 and GII.4 VLPs. CDots with different surface passivation molecules, 2,2′-(ethylenedioxy)bis(ethylamine) (EDA)-CDots and 3-ethoxypropylamine (EPA)-CDots, were synthesized and evaluated. The results indicated both EDA- and EPA- CDots were highly effective to inhibit both strains of VLPs’ bindings to histo-blood group antigens (HBGA) receptors on human cells at CDots concentration of 5 µg/mL, with EDA-CDots achieving 100% inhibition and EPA CDots achieving 85–99% inhibition. At low CDots concentration (2 µg/mL), positively charged EDA-CDots exhibited higher inhibitory effect (~82%) than non-charged EPA-CDots (~60%), suggesting the surface charge status of CDots played a role in the interactions between CDots and the negatively charged VLPs. Both types of CDots also exhibited inhibitory effect on VLP’s binding to their respective antibodies, but much less effective than those to HBGA binding. After CDots treatments, VLPs remained intact, and no degradation was observed on VLPs’ capsid proteins. Taken together, the observed antiviral effects of CDots on noroviruses were mainly through the effective inhibition of VLPs’ binding to HBGA receptors and moderate inhibition of VLPs’ binding to their antibodies, without affecting the integrity of viral capsid protein and the viral particle.